Issues, laws and procedures (2 vol set) - "Gupta,K.R. (ed.)" (New Delhi, 2008)
Special economic zones are specially delineated duty-free enclaves deemed to be foreign territories for the purposes of trade operations, duties and tariffs. Sezs include development of roads, airports, ports, telecom, generation and distribution of power, construction of industrial/commercial/residential complexes, etc. Encouraged by the phenomenal success of seas of people Republic of china$1 (Bwhich first used this model as a measure to attract foreign capital, technology and managerial expertise$1 (Bthe Indian government announced in the exit policy of March 2000, a Scheme for setting up seas in the country. The special economic zones Act, which was enacted subsequently in the year 2005, has been subject to much debate and discussion. From politicians to businessmen, from journalists to social activists have expressed different views thereon. While some have hailed it as a new mantra for export-oriented economic activity, others have criticized it for giving excessive tax and Tariff concessions to see developers. The government is keen to promote the establishment of these large, self-contained areas, supported by world-class infrastructure, oriented towards export promotion. The present book special economic zones: issues, laws and procedures, in two volumes, studies in detail the various aspects of policy relating to sezs. Different problems relating to people apprehensions about these models of displacement of a large number of landowners, environmental pollution likely to be caused by huge industrial units being set up in the sees, the inter-ministerial differences over the issue of unprecedented concessions, incentives and SOPs being given to the developers, etc.$1 (BHave been discussed in the four analytical articles written by economic experts, making valuable suggestions. Besides articles by erudite experts, the book contains documents relating to seas in matters like foreign Trade policy; income Tax, central sales tax, customs duty; circulars and orders of related Ministries, government departments and Reserve Bank of India; and laws and subsequent amendments concerning SEZ policy of the Government. The book includes the land acquisition Act, 1894; National policy for resettlement and rehabilitation of project affected families, 2003; National rehabilitation policy, 2006 and resettlement & rehabilitation policy (NHPC), 2007. Also given in this book are documents containing the policy framework of states. Such wide coverage makes this book a unique treatise on special economic zones. It will prove highly useful for MNCs, SEZ developers, policy make Rs, lawyers, businessmen and students. The General readers will also find it interesting and informative.s
Keywords: SEZ